Design of cost-efficient interconnect processing units : Spidergon STNoC /: Spidergon STNoC. (2018) - Coppola, Marcello; Grammatikakis, Miltos D; Locatelli, Riccardo; Maruccia, Giuseppe; Pieralisi, Lorenzo
No abstract available